If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3z + -1(10) = 1 Multiply -1 * 10 3z + -10 = 1 Reorder the terms: -10 + 3z = 1 Solving -10 + 3z = 1 Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '10' to each side of the equation. -10 + 10 + 3z = 1 + 10 Combine like terms: -10 + 10 = 0 0 + 3z = 1 + 10 3z = 1 + 10 Combine like terms: 1 + 10 = 11 3z = 11 Divide each side by '3'. z = 3.666666667 Simplifying z = 3.666666667
| log(12x^4)-log(2x^3)=2 | | 4(5+7b)+6b=-252 | | cos(x)=-0.5 | | 5ln(x-11)-3=7 | | 8x^2-6x-3=0 | | 3(5-15)=m-5 | | 3x+25=12x+83 | | 3a-1(-1)=-5 | | 4(3y-3)-2y=-9 | | 4v+-3v-4=13 | | 6x^2-2x^3-4x=0 | | 2k-16-10k=-2k | | 207-7x=38x+22 | | -12-3+9= | | 6(x+4)-(2x-8)= | | 5-(-8)=x | | y^2-5y-3=0 | | 5(d-6)+6= | | 2m^3-5m^2-12m=0 | | (2x-3)+(x^2-4x)=180 | | 5x^2+3x-16=32-31x | | -3u+8=14 | | c-(-2)=68 | | 3y+4=-20 | | 56=4y | | 50=(x+10)x | | [(5*6-4)-20]= | | 2a+10=26 | | c+-52=68 | | x-9.51=2.4 | | -2b+8=-8 | | 241=5(5-7x)+8x |